STUDI PERSAINGAN USAHA TOKO RITEL TRADISIONAL DAN TOKO RITEL MODERN DI DESA SUNGAI DANAU KECAMATAN SATUI KABUPATEN TANAH BUMBU KALSEL - Sukma Indah; Aris Soelistyo; M. Sri Wahyudi Suliswanto (Program Studi Ekonomi Pembangunan, 2019)
The purpose of this study is to find out how the competition conditions of traditional retail stores with the presence of modern retail store businesses in Sungai Danau Village. in Sungai Danau Village. The method applied in this study is a qualitative descriptive analysis, further utilizing SWOT analysis to compile the strategy upon increasing the store traditional ritel competition. Apparently, the presence of the modern retail store does not make these entire traditional retail store experiencing huge decline in their sales and there were even some traditional retail store stating that the presence of this modern retail store has affected them positively, forcing them to create an innovation in their stores to keep up with the current market trends. On the average, the strategy that has been done by these small stores. Total score from factor of internal strategy is 3,00 and total score from factor of external strategy is 2,65 and highest variabel from SWOT analysis is IFAS 2,25 and EFAS 2,00. And the strategy that can be done is the S-O Strategy through the build of a one stop shopping concept and the consistent use of direct services. S-T Strategy by maintaining a good relationship with customers, the shop reputation by selling low-priced products and the making of service standardization. W-O Strategy by utilizing assistance from cooperatives and extending the networks and finding supplies in low-cost places. W-T strategy by improving service quality as an attempt to retain customers. Keywords: Competition, Modern Retail Store, Traditional Retail Store Strategy.